Coats Disease in 9 Patients: A Hispanic Case Series - Barrera-Sánchez, Maximiliano; Martinez-Muñoz, Rosa E.; Ruiz-Lozano, Raul E.; Busch, Catharina; Paez-Garza, Juan Homar; Rodriguez-Valdes, Patricio J. (Klinische Monatsblätter für Augenheilkunde, 2021)
Background/Aim To describe demographic and clinical characteristics, treatment, and visual prognosis of Coats disease in Hispanic patients.Methods A retrospective chart review was performed on nine patients (ten eyes) diagnosed with Coats disease in our two clinical centrers from 2004 – 2017.Results Mean age at diagnosis was 5.5 years (range 1 – 12 years) and mean follow-up time was 48 months (range 9 – 108 months). Eight patients (89%) were male and had unilateral disease and one (11%) female patient had bilateral disease. In 40% of the cases, patients were asymptomatic. Visual acuity at first presentation was worse than hand motion in 60% of the eyes. Half of the eyes (5/10 eyes, 50%) had exudative retinal detachment (≥ stage IIIA). Vascular ablation with cryotherapy combined with retinal photocoagulation was the most frequent therapeutic approach (40%). Despite anatomical success at 6 months in 100% of the treated eyes, visual outcome at 1 year of treatment was poor (worse than 20/200) in 70% of the cases.Conclusions In our case series, patients were mostly asymptomatic on presentation, with severe stages of Coats disease. Even with anatomical success after surgical treatment in all treated cases, long-term visual prognosis remained very limited.
Keywords: Coats disease; cryotherapy; exudative retinal detachment; Hispanics; subretinal fluid drainage; vascular ablation